Finite Element Modelling on The Tensile Performances of Boxed-Flange Cold-Formed Steel C- Section Connections - Nazeri, Fatin Khadijah; Kamarudin, A F (Journal of Structural Monitoring and Built Environment, 2025)
Cold-formed steel (CFS) has gained significant attention due to its high strength-to-weight ratio, cost-effectiveness, and ease of fabrication. This study focuses on finite element modeling (FEM) of boxed-flange connections in CFS C-sections under tensile loading, using WELSIM software to simulate structural behavior. The research validates FEM results against experimental data, performs a parametric study on steel thickness and number of screws, and compares failure modes to optimize connection design. The findings indicate that increasing steel thickness and screws enhances load-bearing capacity and delays failure onset. The FEM model predicted a yield load of 24.23 kN for 1.00 mm thick connections with 4 screws, closely matching the experimental result of 23.50 kN. For 0.75 mm thick connections with 2 screws, the FEM model predicted 6.87 kN, compared to the experimental 7.00 kN. These results validate the efficiency of numerical modeling for structural optimization.